Manipulating directional cell motility using intracellular superparamagnetic nanoparticles1. Issue 11 (21st March 2015) - Bradshaw, Michael; Clemons, Tristan D.; Ho, Diwei; Gutiérrez, Lucía; Lázaro, Francisco J.; House, Michael J.; St. Pierre, Timothy G.; Fear, Mark W.; Wood, Fiona M.; Iyer, K. Swaminathan
<x xml:space="preserve">Abstract</x> Intracellular magnetic nanoparticles can be used to manipulate the direction of migrating keratinocytes and regulate the speed of migrating fibroblasts.